Eurasian J Med 2021
DOI: 10.5152/eurasianjmed.2021.20357
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of VATS and Thoracotomy Results in Mediastinal Neurogenic Tumors

Abstract: Objective In this study, we aimed to compare the results of patients who underwent surgery by thoracotomy and Video-assisted thoracoscopic surgery (VATS) in mediastinal neurogenic tumors. Materials and Methods Twenty-six consecutive cases (12 males and 14 females; mean age 39.4 ± 22.3 years; range 1–72 years) who were histopathologically diagnosed as having mediastinal neurogenic tumors between January 2000 and August 2020 were included in a single-center, retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Previous studies suggested that endoscopic surgery was not suitable for children <6 months old, weight <8 kg, tumor/chest index (tumor diameter/tumor horizontal chest diameter) >0.5, tumor diameter >8cm, and tumors located at the costophrenic angle, top of chest, and neck–thorax junction. 11 , 12 However, with the gradual refinement of minimally invasive surgery and anesthesia, the scope for minimally invasive technology has increased. In this study, mediastinal masses located at the top of the chest and the junction of the neck and chest as well as mediastinal tumors with diameters up to 11 cm were successfully resected by thoracoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies suggested that endoscopic surgery was not suitable for children <6 months old, weight <8 kg, tumor/chest index (tumor diameter/tumor horizontal chest diameter) >0.5, tumor diameter >8cm, and tumors located at the costophrenic angle, top of chest, and neck–thorax junction. 11 , 12 However, with the gradual refinement of minimally invasive surgery and anesthesia, the scope for minimally invasive technology has increased. In this study, mediastinal masses located at the top of the chest and the junction of the neck and chest as well as mediastinal tumors with diameters up to 11 cm were successfully resected by thoracoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“… Children with tumor/chest index (tumor diameter/tumor horizontal chest diameter) ≤0.5 can be selected for surgery. 12 , 13 , 14 For children with tumor/chest index ≥0.5, thoracoscopic surgery is not absolutely suitable. The specific tumor characteristics, such as location at the relatively superficial position of the mediastinum, towards one side in the chest or with no important organ coating on its surface, will determine whether or not thoracoscopic surgery can be attempted (Figure 3a,b ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations